2012
DOI: 10.1002/app.38164
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of silver‐ and copper‐charged polypropylene feed spacers for biofouling control

Abstract: Implementation of nanofiltration (NF) and reverse osmosis (RO) processes in treating traditional water sources can provide a steady-state level of removal that eliminates the need for regeneration of ion exchange resins or granular activated carbon. Moreover, RO can help meet future potable water demands through desalination of seawater and brackish waters. The productivity of membrane filtration is severely lowered by fouling, which is caused by the accumulation of foreign substances on the surface and/or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The data obtained from our metal analysis confirm that membranes exposed to UV reducing conditions retain more silver compared to membranes, which were not reduced. Moreover, our study showed that IDA did not contribute to the stability of Ag attachment, which confirms findings reported by others [48].…”
Section: Discussionsupporting
confidence: 93%
“…The data obtained from our metal analysis confirm that membranes exposed to UV reducing conditions retain more silver compared to membranes, which were not reduced. Moreover, our study showed that IDA did not contribute to the stability of Ag attachment, which confirms findings reported by others [48].…”
Section: Discussionsupporting
confidence: 93%
“…Results indicated that the copper-charged feed spacers affected the cellular attachment of the bacteria by hindering the EPS (polysaccharide) secretion. This decreased cellular attachment ultimately resulted in lower flux decline observed [20].…”
Section: Stokes Radius (Nm)mentioning
confidence: 91%
“…This is probably due to a lack of affinity of AgNPs to nonpolar PP. In the literature, it is common to find studies of the surface treatments of the films and subsequent conditions for the anchoring of nanoparticles of silver, silver oxide, zinc oxide, titanium dioxide, cooper and titanium dioxide, copper and silver …”
Section: Introductionmentioning
confidence: 99%